2021
DOI: 10.3389/fimmu.2021.668758
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Roles of CXCR4 in Wound Repair and Regeneration

Abstract: Wound healing is a multi-step process that includes multiple cellular events such as cell proliferation, cell adhesion, and chemotactic response as well as cell apoptosis. Accumulating studies have documented the significance of stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor 4 (CXCR4) signaling in wound repair and regeneration. However, the molecular mechanism of regeneration is not clear. This review describes various types of tissue regeneration that CXCR4 participates in and how the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 97 publications
(136 reference statements)
1
23
0
Order By: Relevance
“…This function of the CXCR4–CXCL12 axis plays a prominent role in the recruitment of bone marrow‐derived progenitors to the uterus and endometrium 21,72,73 . It is also operative in the repair and regeneration of multiple non‐reproductive tissues after damage 74–77 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This function of the CXCR4–CXCL12 axis plays a prominent role in the recruitment of bone marrow‐derived progenitors to the uterus and endometrium 21,72,73 . It is also operative in the repair and regeneration of multiple non‐reproductive tissues after damage 74–77 …”
Section: Discussionmentioning
confidence: 99%
“…21,72,73 It is also operative in the repair and regeneration of multiple non-reproductive tissues after damage. [74][75][76][77] While CXCL12 is essential in activating inflammatory pathways that lead to PTL, CXCL12 also activates an accompanying repair mechanism; the later involves recruitment of progenitors to repair damage after infection or other insult. Proper timing of CXCR4 inhibition in the treatment of PTL may need to include reversal after control of infection, thus reactivating recruitment of progenitor cells involved in tissue repair.…”
Section: Smc-cm Induce Macrophage Function Through Cxcl12/cxcr4 Signa...mentioning
confidence: 99%
“…Given the relevance of CXCL12 for the behavior of EPCs and SMCs as well as processes related to vascular homeostasis [ 10 , 30 , 31 ], we first evaluated the pattern of CXCL12 expression and release by EPCs and SMCs. We found that, similar to DNA damage and tissue hypoxia [ 8 , 32 ], the mechanical disruption of the SMC network increases CXCL12 release, indicating a stress-triggered induction of CXCL12 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotactic growth factors, cytokines, and chemokines concentration gradient, as well as the alignment of the fibrils in the ECM and provisional matrix, control the direction of fibroblast migration. Rather than crossing these fibrils, fibroblasts prefer to move along them [ 26 , 27 ]. To help them move through the matrix, fibroblasts produce proteolytic enzymes on a local level.…”
Section: The Process Of Wound Healingmentioning
confidence: 99%